2023
DOI: 10.1002/solr.202200954
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Monolithic Two‐ and Three‐Terminal Perovskite/Silicon Tandem Solar Cells Under Varying Illumination Conditions

Abstract: Research on perovskite/silicon tandem solar cells is chiefly focused on devices in either two‐ or four‐terminal configurations (2T and 4T, respectively). Straying from these commonly investigated approaches, an alternative monolithically integrated device architecture using three terminals (3T) by combining a semi‐transparent perovskite top cell with a silicon heterojunction bottom cell featuring interdigitated rear contacts is presented. In the presence of a p/n recombination junction between subcells, a quas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The characterization procedure to extract the efficiency map is described in detail in ref. [25]. The same perovskite top cell stack has also recently been used in a high‐efficiency 2T TSC [ 38 ] with hole‐collecting contact as described in ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization procedure to extract the efficiency map is described in detail in ref. [25]. The same perovskite top cell stack has also recently been used in a high‐efficiency 2T TSC [ 38 ] with hole‐collecting contact as described in ref.…”
Section: Resultsmentioning
confidence: 99%
“…[4] Limitations of the detailed balance limit and a comparison to other theoretical efficiency limits are reported by Markvart. [6] In this article, we investigate the detailed balance limit of three-terminal tandem solar cells (3T TSCs), which have recently gained scientific interest, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and for which a record PCE above 29% (certified at 29.56% in two-terminal operation) was presented. [24] For a comprehensive overview of the different types and loading topologies of 3T TSCs, see Warren et al [17] An overview of the two types of 3 T TSCs that are considered in this article is given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum PCE, at 24.9% in the experiment, was achieved when the photocurrent reached a maximum, regardless of the effect of current matching. Additionally, the voltage was unrelated to the spectral, improving the robustness [18].…”
Section: Innovative Structuresmentioning
confidence: 99%
“…Many reports have investigated the integration of MHPs with Si solar cells due to the commercial availability of the latter technology [ 16 , 17 , 18 ]. These studies have shown promising results in terms of power conversion efficiency for planar structures [ 19 , 20 ] and different tandem architectures [ 21 , 22 ]. Raja et al focused on the integration of perovskite nanostructures with Si [ 23 ], obtaining a 21% power conversion efficiency enhancement with respect to the planar counterpart.…”
Section: Introductionmentioning
confidence: 99%